Therapeutic inertia amongst general practitioners with interest in diabetes. Issue 1 (February 2018) - Seidu, Samuel; Than, Tun; Kar, Deb; Lamba, Amrit; Brown, Pam; Zafar, Azhar; Hussain, Rizwan; Amjad, Ahmed; Capehorn, Mathew; Martin, Elizabeth; Fernando, Kevin; McMoran, Jim; et al.
Highlights: Inertia was studied amongst primary care clinicians with an interest in diabetes. The prevalence of therapeutic inertia was 22.1%. None of the characteristics assessed was predictive of therapeutic inertia. Abstract: Introduction: As the therapeutic options in the management of type 2 diabetes increase, there is an increase confusion among health care professionals, thus leading to the phenomenon of therapeutic inertia. This is the failure to escalate or de-escalate treatment when the clinical need for this is required. It has been studied extensively in various settings, however, it has never been reported in any studies focusing solely on primary care physicians with an interest in diabetes. This group is increasingly becoming the focus of managing complex diabetes care in the community, albeit with the support from specialists. Methods: In this retrospective audit, we assessed the prevalence of the phenomenon of therapeutic inertia amongst primary care physicians with an interest in diabetes in UK. We also assessed the predictive abilities of various patient level characteristics on therapeutic inertia amongst this group of clinicians. Results: Out of the 240 patients reported on, therapeutic inertia was judged to have occurred in 53 (22.1%) of patients. The full model containing all the selected variables was not statistically significant, p = 0.59. So the model was not able to distinguish between situations in which therapeutic inertia occurred and when it did not occur. None of the patient level characteristics on its own was predictive of therapeutic inertia. Conclusion: Therapeutic inertia was present only in about a fifth of patient patients with diabetes being managed by primary care physicians with an interest in diabetes.